Verification of the Theoretical Basis for Determining the Curvature of the Track Axis Using the Moving Chord Method - Koc, Wladyslaw (European Journal of Applied Sciences, 2023)
The paper indicates the possibility of a new approach to the problem of identifying the measured railway route. The currently used methods of identifying the track axis have been characterized, which consist in generating an optimized geometrical layout in the tested area by minimizing the occurring deviations of this layout from the measurement points. The proposed new approach uses the obtained measurement data to determine the existing curvature of the geometric layout. This paper presents a short review of the current activities related to the determination of the curvature of model geometrical layouts and the operated railway track using a new method of determining the curvature, known as the moving chord method. The demonstrated high efficiency of this method should not, however, obscure the fact that the assumptions adopted in it apply – generally speaking – only to a certain, limited range of geometric parameters. The presented analysis showed that the adopted assumptions could be applied to the railway track, because it uses large radii of circular arcs (of the order of several hundred or several thousand meters) and transition curves with a very mild change in curvature. However, the condition must be met that in the calculation procedure appropriate lengths of the moving chord will be used, increasing as the radius of the circular arc increases. Using the test geometric layout, it was clearly demonstrated that the discretization of data used in the moving chord method does not affect the accuracy of the obtained curvature values at individual measurement points.